O Deus das urnas: discurso religioso nas campanhas de Lula e Bolsonaro à Presidência em 2022 - Belloube, Fabiano Garcia Mascarenhas (2023)
Throughout the 2022 presidential election, religious discourse was systematically employed to capture a segment of the electorate with record influence on institutional politics ("politicized religious voters", i.e., voters whose support for candidates is based mainly on religious reasons). This research proposes to investigate in which ways discourse strategies employed by the two main presidential candidates towards this audience converged and in which ways they diverged. To this end, the analysis of each electoral round was divided into two moments: first, a mapping of each candidate's incentives, in which an adaptation of the Selectorate Theory advocated by Bueno de Mesquita et al was employed; then, a contente analysis of the speeches based on six authorial axes of analysis. In relation to the first round, it was concluded that both candidates used similar discourse tools, but in diferente proportions depending on the political incentives on each one. In the second round, these proportions approached the point of being virtually similar. Nevertheless, although discursive tools themselves were analogous, it was concluded that their content differed considerably from one candidate to another (e.g., both candidates sought to associate political agendas with Christian doctrine, but in relation to antagonistic agendas)